Restructuring of the Iranian tense/aspect/mood system - Bubenik, Vit; Ziamajidi, Leila (Lingua Posnaniensis, 2018)
Special attention will be paid to the rise of the analytic Perfect in Middle Persian and its further development in Early New Persian and other West Iranian languages. It will be shown that the degrammation of the copula played a significant role in the formation of compound temporal (Perfect, Pluperfect) and modal categories (Evidential, Conjectural) in New Persian, Kurdish, Balochi and Tajik. The Evidential mode of New Persian is based on the analytic Perfect rafte ast ‘he is gone’ and it is found in all the three aspectual categories (Imperfective, Perfective and Perfect) and both voices. It is usually claimed that it developed in the Iranian languages probably under Turkic influence. We intend to address the contentious issue of syntactic borrowing in terms of language contact in another paper.